Failure Mode Analysis and Maintenance of Railway Overhead Line Rigid Stainless Steel Droppers and Multi-Strand Copper Jumpers - Jingyu Du; Jian-Ping Li; George Chaplin; Andrew Gardiner; Fun-Yim Hu (IET Electrical Systems in Transportation)
Droppers and jumpers are important components of railway overhead line electrification. Their effective maintenance is critical for the railway’s safe and reliable operation; the consequences of their failure can be disproportionally serious. This paper systematically analyses the components’ failure by applying the method of failure modes and effects analysis to the maintenance records and incident statistics of Britain’s East Coast Main Line. The analysis is presented with photographic evidence and a review of the current maintenance strategy and practice that addresses the risk of failure. These results can support improved dropper and jumper design and the development of more effective maintenance strategies to further prevent failure and operational disruption.